Prevalence of gestational diabetes mellitus and associated factors in Southern Ethiopia - Eskinder Wolka Woticha; Wakgari Deressa; Ahmed Reja (Asian Journal of Medical Sciences, 2018)
Background: Presence of gestational diabetes mellitus during pregnancy has serious complications for both mother and child. Its burden is increasing in low and middle-income countries but, little is known about its contribution in Ethiopia.